2014
DOI: 10.1158/0008-5472.can-13-1778
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Targets Breast Cancer Stem–like Cells with Microtentacles That Persist in Mammospheres and Promote Reattachment

Abstract: Cancer stem-like cells (CSC) and circulating tumor cells (CTCs) have related properties associated with distant metastasis, but the mechanisms through which CSCs promote metastasis are unclear. In this study, we report that breast cancer cell lines with more stem-like properties display higher levels of microtentacles (McTNs), a type of tubulin-based protrusion of the plasma cell membrane which forms on detached or suspended cells and aid in cell reattachment. We hypothesized that CSCs with large numbers of Mc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 51 publications
3
62
1
Order By: Relevance
“…But at the same time, it also calls to attention the possible implications of using ROCK inhibitors as cancer therapeutics if they promote survival and possibly conversion of detached tumor cells towards a stem-like phenotype. We have recently reported that breast cancer cell lines with higher stem-like characteristics have increased McTNs that promote their reattachment from suspension [57]. These findings indicate that chemotherapeutics that inadvertently promote such stem-like characteristics might be detrimental to overall progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…But at the same time, it also calls to attention the possible implications of using ROCK inhibitors as cancer therapeutics if they promote survival and possibly conversion of detached tumor cells towards a stem-like phenotype. We have recently reported that breast cancer cell lines with higher stem-like characteristics have increased McTNs that promote their reattachment from suspension [57]. These findings indicate that chemotherapeutics that inadvertently promote such stem-like characteristics might be detrimental to overall progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is severely toxic to normal tissues at high dose, which limits its use in cancer therapies [19]. Colchicine showed diferent antitumoral efects which include inhibition of metastatic potential [20] and angiogenesis [21], cell blebbing through a Rho/Rho efector kinase (ROCK)/ myosin light-chain kinase (MLCK) pathway [22], decrease of ATP inlux into mitochondria [23].…”
Section: Microtubule-destabilizing Agentsmentioning
confidence: 99%
“…Interestingly, it was found that curcumin could inhibit mammosphere formation and could also decrease the amount of aldehyde dehydrogenase-positive cells in normal and malignant breast cancer cells through the inhibition of Wnt signaling (23), suggesting the inhibitory effects of curcumin on breast cancer stem cells (23). Curcumin has also been found to inhibit the expression of several molecules in Wnt/␤-catenin pathway including disheveled, ␤-catenin, cyclin D1, and slug in both MCF-7 and MDA-MB-231 breast cancer cells (23). Immunofluorescence staining showed that curcumin significantly reduced the nuclear expression of disheveled and ␤-catenin proteins.…”
Section: Natural Products and Human Healthmentioning
confidence: 99%